Problematyka handlu zagranicznego w rozważaniach polskich merkantylistów - Danowska-Prokop, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Przedstawiciele doktryny merkantylizmu (kapitalizmu kupieckiego) zaproponowali nowe spojrzenie na politykę gospodarczą, w tym na rolę handlu zagranicznego w tworzeniu i pomnażaniu bogactwa, w rozwoju sił wytwórczych. W ich ujęciu polityka gospodarcza powinna być prowadzona w duchu interwencjonizmu i protekcjonizmu celnego. Merkantyliści, uzasadniając ekonomiczną i polityczno-militarystyczną ekspansję państwa, opowiadali się zarówno za ochroną handlu i rodzimej produkcji (zwłaszcza przemysłowej), jak i za ochroną własnego rynku przed konkurencją zewnętrzną. Dlatego też z jednej strony popierali politykę proeksportową, a z drugiej, wspierali politykę antyimportową. Uwarunkowania gospodarczo-demograficzne w Europie Zachodniej zadecydowały o rozwoju gospodarki folwarczno-pańszczyźnianej w XVI-wiecznej Polsce. Jednak zamiana wskaźnika terms of trade w XVII w. uruchomiła mechanizm odwrotny, opłacalność produkcji rolnej systematycznie malała i dlatego wzrosło zainteresowanie koncepcją „zwarcia granic”.

Representatives of the doctrine of mercantilism (merchant capitalism) proposed a new look at economic policy, including the role of foreign trade in the creation and multiplication of wealth, in the development of productive forces. In their view, economic policy should be conducted in the spirit of interventionism and customs protectionism. The mercantilists, justifying the economic and political-militaristic expansion of the state, advocated both the protection of trade and domestic production (especially industrial), and the protection of their own market against external competition. Therefore, on the one hand, they supported a pro-export policy, and on the other hand, they supported an anti-import policy. Economic and demographic conditions in Western Europe determined the development of the manor and serf economy in Poland. The growing demand for agricultural products triggered the mechanism of wealth growth, which translated into improved farming conditions in agriculture. The change of the terms of trade index in the 17th century triggered the reverse mechanism, the profitability of agricultural production was systematically decreasing.
The issue of foreign trade in the considerations of Polish mercantilists
Keywords: handel zagraniczny; eksport; import; merkantylizm; foreign trade; exports; imports; mercantilism